Adaptive and Innate Immune Responsiveness to Borrelia burgdorferi sensu lato in Exposed Asymptomatic Children and Children with Previous Clinical Lyme Borreliosis - Barbro H. Skogman; Sandra Hellberg; Christina Ekerfelt; Maria C. Jenmalm; Pia Forsberg; Johnny Ludvigsson; Sven Bergström; Jan Ernerudh (Clinical and Developmental Immunology)
Why some individuals develop clinical manifestations in Lyme borreliosis (LB) while others remain asymptomatic is largely unknown. Therefore, we wanted to investigate adaptive and innate immune responsiveness to Borrelia burgdorferi sensu lato in exposed Borrelia-antibody-positive asymptomatic children (n=20), children with previous clinical LB (n=24), and controls (n=20). Blood samples were analyzed for Borrelia-specific interferon (IFN)-γ, interleukin (IL)-4, and IL-17 secretion by ELISPOT and Borrelia-induced IL-1β, IL-6, IL-10, IL-12(p70), and tumor necrosis factor (TNF) secretion by Luminex. We found no significant differences in cytokine secretion between groups, but a tendency towards an increased spontaneous secretion of IL-6 was found among children with previous clinical LB. In conclusion, the adaptive or innate immune responsiveness to Borrelia burgdorferi sensu lato was similar in Borrelia-exposed asymptomatic children and children with previous clinical LB. Thus, the immunological mechanisms of importance for eradicating the spirochete effectively without developing clinical manifestations of LB remain unknown.